Smart tourism economics: introducing a technology-driven competitive advantages framework - Anica-Popa, Liana-Elena; Petrică (Papuc), Iuliana-Mădălina; Caraiani, Chirața; Lungu, Camelia-Iuliana (Journal of Business Economics and Management, 2025)
Recently, in the Hospitality 5.0 era, the Smart Tourism industry has experienced disruptions due to the widespread integration of cutting-edge technologies (Artificial Intelligence, Internet of Things, Robots, Big Data, and others) enabling the overall tourist experience enhancement. This study aims to identify the main clusters of technologies adopted and to highlight the competitive advantages resulting from their implementation in Smart Tourism. A meta-analysis was conducted on a final WoS sample of 60 papers published between 2015 and 2023. Four synoptic tables showcase the technologies, the processes they facilitate, the competitive advantages, and the smart destinations where they have been implemented. The originality of this research consists of the 70 competitive advantages identified across the industry, leveraged in designing the CECoR map (Customer Experience, Costs, Revenues) and the CAdSTT framework (Competitive Advantage-driven Smart Tourism Technologies). Guidelines for supporting managers in planning and initiating projects aiming at integrating technology to increase organisational value were proposed.